MARABI NIGHTS: EARLY SOUTH AFRICAN JAZZ AND VAUDEVILLE, by Cristopher Ballantine, Ravan Press, Johannesburg, 1993, 1 l6pp, with cassette. - Allen, Lara (International Library of African Music, 1996)
pages: 109-110
Keywords: South Africa; African Music